Between Social Media and Print: Shifts in Reading Preferences of FISIP UNTAN Pontianak Students in the Era of Information Floods - Julia Magdalena Wuysang; Ira Patriani; Feibe Engeline Pijoh; Rafik (Technium Social Sciences Journal, 2025)
This study explores the dynamics of changing reading preferences among FISIP UNTAN Pontianak students in the context of the competition between social media and print media amid the digital information flood. Changes in students’ information consumption patterns are not merely behavioral but also reflective of the structures of information distribution, access, and academic literacy. The study employs a qualitative phenomenological approach to understand students’ subjective experiences, with data collected through in-depth interviews and participant observation, subsequently analyzed using thematic analysis (Braun & Clarke, 2006) to identify key media consumption themes. The findings reveal four main insights. First, shifts in reading preferences due to social media dominance, where students prefer fast information via digital platforms, reflecting a redistribution of informational power and decreased print media consumption (Chomsky, 1997; McChesney, 2013). Second, information overload and academic literacy challenges, showing that digital information floods affect students’ ability to critically analyze and evaluate sources (Levitin, 2014). Third, disparities in access and socio-digital capital, where unequal access to technology and social networks creates opportunities and barriers to academic information (Castells, 2009; van Dijk, 2020). Fourth, erosion of deep reading habits, as social media dominance and preference for quick information reduce engagement with more in-depth print sources, impacting academic comprehension (Levitin, 2014; Bauerlein, 2008). These findings have important implications for higher education, including the development of academic communication strategies that combine the speed of social media with the depth of print media, and strengthening students’ critical literacy to navigate the complexities of digital information floods. The study provides insights into the interplay between social media and print in shaping students’ information consumption behaviors and reading preferences in Indonesia.